Quantitative Analysis of Abdominal Muscles Using Elastography in Female Patients With Incisional Hernia - Wang, Bo; He, Kai; Zhu, Yulan; Fu, Xiaojian; Yao, Qiyuan; Chen, Hao; Wang, Xiaohong (Frontiers in Surgery, 2022)
This study aimed to assess the thickness and shear wave speed (SWS) of the anterolateral abdominal wall muscles in female patients with incisional hernias of different widths, in order to analyze the biomechanical properties of abdominal wall muscles. This study included 53 patients with incisional hernia (Group A [hernia width <4 cm]: 21 patients, Group B [hernia width ≥4 cm]: 32 patients). The muscle thickness and SWS values of the external oblique (EO), internal oblique (IO), and transversus abdominis (TrA), and the hernia width were measured using Siemens Acuson S2000 ultrasound systems. Four detection points were labeled on the anterolateral abdominal wall: points 1, 2, 3, and 4, corresponding to the upper right, upper left, lower right, and lower left, respectively. The muscle thickness of the IO at point 3 was significantly different between both groups (p = 0.024). Group B had significantly higher SWS values than Group A, especially for the EO (points 1, 2, and 3), IO (points 1 and 2), and TrA (points 2 and 4) (p < 0.05). Pearson correlation analysis shows no significant correlation between muscle thickness and the SWS values of EO, IO, and TrA (all p > 0.05). Linear correlation analysis showed a significantly positive correlation between hernia width and the mean SWS value of EO, IO, and TrA (p = 0.004, 0.005, and 0.043, respectively). Muscle thickness was not reliable measure to directly reflect the biomechanical changes of the abdominal wall muscles in patients with incisional hernia. Comparatively, SWE can accurately measure the stiffness of the abdominal wall muscles and intuitively evaluate its biomechanical properties.